Stable Marital Histories Predict Happiness and Health Across Educational Groups - Miika Mäki; Anna Erika Hägglund; Anna Rotkirch; Sangita Kulathinal; Mikko Myrskylä (European Journal of Population, 2025)
Couple relations are a key determinant of mental and physical well-being in old age. However, we do not know how the advantages and disadvantages associated with partnership histories vary between socioeconomic groups. We create relationship history typologies for the cohorts 1945-1957 using the Survey of Health, Ageing, and Retirement in Europe and examine, for the first time, how relationship histories relate to multiple indicators of well-being by educational attainment. The results show that stable marriages predict greater well-being, compared to single and less stable partnership histories. The positive outcomes are similar across all educational groups. Those with lower education who have divorced experience even lower well-being in old age. The interaction analyses suggest that individuals with fewer resources could suffer more from losing a partner. The findings underscore that current and past romantic relationships are linked to well-being in old age and help policymakers identify vulnerable subgroups among the ageing population.
Keywords: 300; Partnership history; Resource substitution; Cumulative disadvantage; Health; Quality of life